ANALISIS REAKSI PASAR ATAS PENGUMUMAN STOCK SPLIT PERUSAHAAN INDEKS IDX80 DAN NON IDX80 - Krisna, I Made Winata; Wirawati, Ni Gusti Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
This study aims to analyze market reactions to stock split announcements that focus on company shares in the IDX80 and Non IDX80 indices. This study uses the Efficient Market Hypothesis and Signaling theories. The study was conducted using an event study for 7 days (t-3 to t+3) of the stock split announcement. The sample of this study consisted of 43 companies with 12 companies included in the IDX80 index and 31 companies included in the Non IDX80 index. The research sample was analyzed using the Paired Sample t-test, and the Wilcoxon Signed Rank Test. The results of the study showed that there was no difference in abnormal returns on stock split announcements in companies in the IDX80 and Non IDX80 indices, but there was a difference in trading volume activity on stock split announcements in companies in the IDX80 and Non IDX80 indices. Theoretically, this study is unable to support the Efficient Market Hypothesis theory, especially those related to abnormal returns but is able to support the signal theory related to trading volume activity. Practically, this study can be a consideration for investors to invest by utilizing the stock split announcement event.